Air pollution control engineering - Nevers, Noel de (McGraw-Hill, 2000)
The book is devoted to control devices in air pollution, their theory and practice. It is also devoted to topics that form some of the background for the selection of such devices: air pollution effects, the structure of U.S. air pollution law, atmospheric models, etc.